Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1371/journal.pone.0079589
|View full text |Cite
|
Sign up to set email alerts
|

A Distinct Boundary between the Higher Brain’s Susceptibility to Ischemia and the Lower Brain’s Resistance

Abstract: Higher brain regions are more susceptible to global ischemia than the brainstem, but is there a gradual increase in vulnerability in the caudal-rostral direction or is there a discrete boundary? We examined the interface between `higher` thalamus and the hypothalamus the using live brain slices where variation in blood flow is not a factor. Whole-cell current clamp recording of 18 thalamic neurons in response to 10 min O2/glucose deprivation (OGD) revealed a rapid anoxic depolarization (AD) from which thalamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 44 publications
6
31
0
Order By: Relevance
“…[14] Among various brain regions, some are more susceptible to brain ischemia due to the high rate of oxidative metabolic activity, intense production of reactive oxygen metabolites, high content of polyunsaturated fatty acids, relatively low antioxidant capacity, low repair mechanism activity, and poor plasticity in that areas. [15]…”
Section: Discussionmentioning
confidence: 99%
“…[14] Among various brain regions, some are more susceptible to brain ischemia due to the high rate of oxidative metabolic activity, intense production of reactive oxygen metabolites, high content of polyunsaturated fatty acids, relatively low antioxidant capacity, low repair mechanism activity, and poor plasticity in that areas. [15]…”
Section: Discussionmentioning
confidence: 99%
“…In ischemia, the magnitude of the change in tissue water content is dependent on the degree of brain injury 56 . Changes in brain extracellular or intracellular water content as a result of exposure to aniso-osmotic, hypoxic, or ischemic conditions alter the optical properties of the tissue, measured here as the IOS 1, 9, 30, 41 . In the present studies, we found a consistent increase in IOS in slices from SARA mice during OGD, similar to our previous studies using brain slices from wild type and R+A+ mice 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Tissue swelling as a measure of brain edema was determined indirectly as we and others previously described 5, 9, 51 by measuring the intrinsic optical signal (IOS) defined as the intensity of transmitted light during OGD treatment expressed as a percent of the intensity measured prior to the start of OGD 5 . Slices were transilluminated using a DC-regulated halogen lamp which delivered white light to the recording stage via a randomized fiber optic bundle.…”
Section: Methodsmentioning
confidence: 99%
“…⁄ p < 0.05, significant; ⁄⁄ p < 0.01, very significant; ⁄⁄⁄ p < 0.001, extremely significant. thalamus-hypothalamus interface represents a discrete boundary, with high thalamic neuronal vulnerability to ischemia (as in the more rostral neocortex, striatum, and hippocampus), and low vulnerability in the hypothalamus (as in the brainstem) [39]. Thus, decreased FU may correlate with increased tolerance to asphyxia.…”
Section: Discussionmentioning
confidence: 99%